Todorov, Levinas and anti-totalitarian humanism: A perspective on contemporary utopian thought - Terreblanche, Salomon J. (HTS teologiese studies, 2007)
This article explores the significance of anti-totalitarian humanism for contemporary moral and social philosophy, with special reference to the thinking of Emmanuel Levinas (1906-1995). Special use is made of Tzvetan Todorov’s (1939) work “Hope and memory” to clarify the framework within which anti-totalitarian humanism takes shape, and also to shed light on the relation, similarities and disagreements between the totalitarian utopianism that characterized twentieth century fascist regimes, and other versions and residues of the utopian tradition, such as we encounter in Levinas and the early generation of Neo-Marxist philosophers. Levinas’ attempt in his early works to develop a humanism that is founded in both everyday material existence and interpersonal relationships is then examined in closer detail. Interpretations of the utopian significance of his phenomenological notions such as death, time and sociality, Messianic hope, despair and moral repair are offered. It is emphasized that Levinas’ early notion of innerworldly bliss constitutes a utopian core in his thought that is to be separate from the notion of innerworldly bliss that characterizes totalitarian utopianism, and also undermines the philosophical foundations of totalitarian utopianism.